Effect of light-emitting diodes on somatic embryogenesis and tissue-cultured plantlet growth of arecanut (Areca catechu) dwarf hybrid VTLAH-2 (Current Horticulture, 2024)
This study was carried out to evaluate the effects of LEDs on embryogenic callus proliferation, somatic embryo formation and tissue  cultured plantlet growth of arecanut (Areca catechu L.) dwarf hybrid (VTLAH-2) at ICAR-CPCRI, Kasaragod, Kerala during 2021- 2022. Yellow, red, blue, white monochromatic LEDs, and a combination of red: blue and blue: yellow with different photosynthetic  photon flux densities (PPFDs 10, 20 and 100 µmol m-2s-1) were used. Eeuwen’s Y3 basal media supplemented with picloram 2.5 µM  were used for multiplication of calli. Embryogenic calli were inoculated to multiplication media, and these plates were kept under  different LED conditions to examine calli multiplication and somatic embryogenesis. To check the growth of plantlets, germinated  somatic embryos were transferred to test tubes containing arecanut plantlet growing media (i.e., 0.5 mg/L BAP +0.5 mg/L NAA  and +0.25 mg/L IBA with Y3 basal medium. Multiplication rate of arecanut embryogenic calli (0.051±0.008 gg-1d-1), somatic embryo  formation (46.1±2.9), plantlet growth (RGR-wt.0.9±0.07 gg-1d-1; RGR-ht: 0.57±0.01 cm.cm-1d-1) and survival (61.4±4.3%) were found  to be superior under a combination of red-yellow LED, which was followed by blue and yellow monochromatic LEDs. Whereas  comparatively lower callus multiplication (0.008±0.001 gg-1d-1) and plantlet growth (RGR-wt: 0.72±0.03 gg-1d-1; RGR-ht: 0.24±0.12  cm.cm-1d-1) was noticed with white and red LEDs with a PPFD values of 100 µmol m-2s-1 and 20 µmol m-2s-1 consecutively. Thus,  there was a positive effect of LED light source on arecanut somatic embryogenesis and plantlet growth.
Keywords: Arecanut (Areca catechu L.); LED; Somatic embryogenesis; Callus multiplication; in vitro plantlet growth